Numerical investigation of the effect of minaret height on its dynamic characteristics - Erkek, Hakan; Yetkın, Musa; Dedeoğlu, İbrahim Özgür (My University, 2023)
Minarets are structures that have an important place in Islamic architecture. Although these structures have a long, thin and delicate appearance, they can be constructed in different cross-sections and heights. Due to their geometry, minarets can be damaged under earthquake and wind loads. In order to minimize the possibility of damage to these structures, they must be constructed with suitable geometry and materials. In this study, the effect of minaret height on dynamic characteristics (natural frequency and mode shape) was investigated numerically. For numerical application, 19 differ-ent minarets with heights ranging from 13.5 m to 33.75 m were modeled in the ANSYS finite element package program. It is assumed that the minarets have as masonry and the base of the minaret was fixed support to the soil. These minarets were evaluated in terms of natural frequency, mode shape and modal mass participation ratios by per-forming modal analyses. In addition, an equation has been derived that can predict the first natural frequency of the minaret depending on its height.
Keywords: Minaret; Natural frequency; Dynamic characteristic; Mode shape; Modal mass participation ratio